TRITICALE REVIEW: NAVIGATING PAST ACHIEVEMENTS, CURRENT REALITIES AND FUTURE HORIZONS IN AGRICULTURAL INNOVATION - Iuliana Cionca; Ioan Lupuț; Teodor Rusu (Agricultura)
The purpose of this paper is to understand the evolution and sustainability of triticale from the perspective of time: past, present and future. This review paper is based on analyzing the specialized literature using a set of keywords, a search that conducted to scientific databases, such as Web of Science, Google Scholar and Scopus. The findings reveal that triticale is more and more cultivated and present in the agriculture topics. Due to its plasticity to adapt at adverse environmental conditions this culture is suitable for growing under poor conditions compared to wheat and other cereal crops. Most of the farmers started to see the advantages of this culture and triticale started to be more visible by being cultivated and also studied. Triticale is the first man-made cereal crop species that combines the positive attributes of wheat and rye.